Ultrasonography B-mode, elastography (acoustic radiation force impulse), color doppler and hysteroscopy uterine in postpartum in Santa Ines sheep - Mariano, Renata Sitta Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The aim of this study was to evaluate the uterine characteristics of Santa Inês sheep during the postpartum period, using mode B-mode ultrasonography, elastography ARFI (acoustic radiation force impulse), Doppler and hysteroscopy, with emphasis on the early diagnosis of reproductive alterations, evaluation of development and regression during this period. Twenty Santa Inês sheep were used and designated after clinical and obstetric evaluation. B-mode, Doppler and elastography ARFI evaluations were performed by transabdominal approach using the Siemens S2000 ultrasound system, with a multi-frequency and convex transducer of 5.0 to 8.0 MHz. Ultrasonography of the uterine structure was performed at immediate postpartum (M0) and sequentially every 48 hours, during 30 days, totaling 16 experimental samples. Ultrasonography characteristics of the uterus (echogenicity, echotexture, and biometry), vascular parameters (color Doppler) and stiffness aspects (qualitative and quantitative elastography) of the uterine structures were evaluated during the postpartum. Hysteroscopy evaluation of the uterine involution of the sheep was performed as follows: immediate moment after lambing (M0) and sequentially every 6 hours, until the moment where the endoscopic access to the uterus through the cervix was no longer possible. Uterine biopsy was performed at the same moments. The experimental design will be completely randomized, with a significance level of 5% for tests performed.

O objetivo deste estudo foi avaliar as características dos tecidos uterinos de ovelhas Santa Inês durante o período pós-parto, por meio da ultrassonografia modo B, elastografia e Doppler e histeroscopia, com ênfase na precocidade do diagnóstico de alterações reprodutivas,avaliação do desenvolvimento e regressão uterina durante esse período. Foram utilizadas 20 ovelhas Santa Inês selecionadas após avaliação clinica e obstétrica. As avaliações ultrassonográficas modo B, Doppler e Elastografia foram realizadas por via trasabdominal com aparelho Siemens S2000, transdutor mulitfrequencial e convexo de 5,0 a 8,0 MHz. Os exames foram realizados entre o período de pós-parto imediato até a total involução uterina, verificando-se as particularidades ultrassonográficas (biometria uterina, ecogenicidade e ecotextura), parâmetros vasculares (Doppler em cores) e aspectos da rigidez (elastografia qualitativa e quantitativa) das estruturas uterinas nesta fase. O acompanhamento pós-parto da estrutura uterina das ovelhas foi realizado em: momento imediato (primeiro dia pós-parto) e sequencialmente a cada 48 horas, durante trinta dias. A histeroscopia e biópsia foram realizadas nos períodos pós-parto imediato, e posteriormente a cada 6 horas, até a total involução cervical. O delineamento experimental foi inteiramente casualizado, com nível de significância de 5% para testes realizados.
Ultrassonografia modo B, elastografia (acoustic radiation force impulse), color doppler e histeroscopia uterina de pós parto em ovelhas Santa Inês
Keywords: Ovine; Ultrasound; Puerperium; Uterus